2021
DOI: 10.3389/fpsyg.2021.712823
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise Reduce the Autonomic Dysfunction of Patients With Cancer and Its Survivors? A Systematic Review and Meta-Analysis

Abstract: Background: Cancer therapies have increased patient survival rates, but side effects such as cardiotoxicity and neurotoxicity can lead to autonomic nervous and cardiovascular system dysfunction. This would result in a decrease in parasympathetic activity and the enhancement of sympathetic activity. Heart rate variability (HRV), which reflects autonomic modulation, is a valuable physiological tool since it correlates with cancer-related fatigue, stress, depression, and mortality in patients with cancer.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…for cancer patients and survivors. Controlled physical activity, mindfulness-based interventions and breathing exercises appear to be effective and have a positive effect on parasympathetic activity (Laborde et al, 2022;Lavín-Pérez et al, 2021;Niederer et al, 2013;Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…for cancer patients and survivors. Controlled physical activity, mindfulness-based interventions and breathing exercises appear to be effective and have a positive effect on parasympathetic activity (Laborde et al, 2022;Lavín-Pérez et al, 2021;Niederer et al, 2013;Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that interventions such as exercise training may help improve HRV and autonomic function with improved cardiorespiratory fitness in cancer patients. 19,20 According to the National Institutes of Health, Yoga is one of the most commonly used complementary therapies, with emerging evidence supporting its use among adults diagnosed with cancer. 43 Yoga practice has been shown to increase the heart rate variability (HRV) by increasing activity of the parasympathetic nervous system (PNS) and reducing stress and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes were also found in the LF and the LF/HF ratio between exercise and control groups. Also, beneficial changes may occur with resistance and endurance workouts [92].…”
Section: Exercise Practicementioning
confidence: 99%